(3CejQI GdZRdGf GdUZjQI (B:s (3McGjGJ TYHjI ef GdOGfeGQc (B/s - (3ZQhfOajZ, Sajf s 1824-1883; (3Ybd, QhRjGs ((3CHh XHj (B:s (3gjFI CHh XHj ddKbGaI hGdJQGK, s (3eTQhY cdeI,s, 2010)
(3JJeJY GdbUU GdTYHjI GdOfeGQcjI HNGUjI eROhLI aaj GdhbJ GdPj JMJd ajgG GdNhGQb hGdHWhdGJ hbUU GdMH GdeSJMjdI hGdfHjdI hGdSMQI hGdSGMQGJ MjRG cHjQG , Ydi ZQGQ eG fLO aj eYXe GdbUU GdTYHj GdYGdej , gPg McGjGJ dcd GdCYeGQ fLO ajgG eG jJbGWY hjJTGHI eY GdehQhK GdMcGFj GdYGdej , HbOQ eG fLO ajgG GdYfGUQ GdeMdjI GdOfeGQcjI , hfLO ajgG GdCNdGbj hGdhYXj HbOQ eG fLO GdSMQj hGdaGfJGRj , dJLeY Hjf eNJda GdYfGUQ GdJj JTcd GdMcGjGJ GdTYHjI GdMbjbI , GdJi JSJWjY GdUehO CeGe GNJHGQ GdRef hGdGfJbGd ef Ljd Edi Ljd hef ecGf Edi CNQ (B.s
Keywords: (3GdbUU GdOfeGQcjI GdTYHjIs -- (3JQLeGJ Edi GdYQHjIs -- (3CSGWjQs -- (3GdOfeGQcs